2004
DOI: 10.1207/s15327914nc5002_11
|View full text |Cite
|
Sign up to set email alerts
|

Cruciferous Vegetables, Genetic Polymorphisms in Glutathione S-Transferases M1 and T1, and Prostate Cancer Risk

Abstract: Cruciferous vegetables contain anticarcinogenic isothiocyanates (ITCs), particularly the potent sulforaphane, which may decrease risk of prostate cancer through induction of phase II enzymes, including glutathione S-transferases (GSTs). We evaluated this hypothesis in a population-based, case-control study of prostate cancer, including 428 men with incident prostate cancer and 537 community controls. An in-person interview included an extensive food-frequency questionnaire. Genotyping for deletions in GSTM1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(118 citation statements)
references
References 29 publications
3
109
1
2
Order By: Relevance
“…Four out of eight casecontrol studies published since 1990 found that some measure of cruciferous vegetable intake was significantly lower in men diagnosed with prostate cancer than men in a cancer-free control group [47][48][49][50]. Of the 4 prospective cohort studies that have examined associations between cruciferous vegetable intake and the risk of prostate cancer, none found statistically significant inverse associations overall [51][52][53][54].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Four out of eight casecontrol studies published since 1990 found that some measure of cruciferous vegetable intake was significantly lower in men diagnosed with prostate cancer than men in a cancer-free control group [47][48][49][50]. Of the 4 prospective cohort studies that have examined associations between cruciferous vegetable intake and the risk of prostate cancer, none found statistically significant inverse associations overall [51][52][53][54].…”
Section: Prostate Cancermentioning
confidence: 99%
“…For instance, consumption of a known amount of the phytonutrient sulforaphane does not guarantee absorption of a predicted amount of anti-cancer molecule since differences in the glutathione S transferase M1 gene influences the metabolic rate of sulforaphane, a phytonutrient present in broccoli. The faster it is metabolized, the faster it is expelled from the body , Gasper et al 2005, Gross-Steinmeyer et al 2010, Joseph et al 2004, Lampe 2007, Lampe 2009, McWalter et al 2004, Riedl, Saxon and Diaz-Sanchez 2009, Ritz, Wan and Diaz-Sanchez 2007, Traka et al 2008. Similarly, a number of the nutrients, e.g.…”
Section: Dietmentioning
confidence: 99%
“…A 2002 review has concluded that the epidemiological literature provides modest support for the premise that high cruciferous vegetable intake lowers prostate cancer risk (48) . The examples are case-control studies (49)(50)(51)(52) . Two studies have previously reported inverse associations for cruciferous vegetables, with marked reductions in risk for high cruciferous vegetable intake v. low intake (49,52) .…”
Section: Prostate Cancermentioning
confidence: 99%